COVID-19–RELATED LUNG INJURY: A HISTOPATHOLOGICAL OVERVIEW - Alkhirsan, Zainab M Jawad; Alyasiry, Esraa A.; Abdulhadi, Ali M Hussein (Journal of Medical Genetics and Clinical Biology, 2026)
Objective: To provide a comprehensive review of the key histopathological features associated with COVID-19–related lung injury and to clarify the extent of vascular and inflammatory involvement in the disease. Method: A literature review analyzing reported histopathological findings in COVID-19 lung specimens, comparing them with other viral infections such as H1N1 influenza, and correlating them with clinical and radiological data. Results: Findings consistently highlight diffuse alveolar damage (exudative and proliferative phases), type II pneumocyte hyperplasia, squamous metaplasia, intra-alveolar hemorrhage, microthrombosis, and occasional osseous metaplasia. Additional observations include inflammatory infiltrates, endothelial injury, and cytokine-related damage (e.g., IL-6 upregulation). COVID-19 shows more extensive alveolar and vascular involvement than many other viral infections, though findings vary across patients and comorbidities. Novelty: The review underscores that although several histopathological features overlap with other viral pneumonias, the severity of vascular injury and the complexity of the inflammatory response in COVID-19 distinguish it. It also stresses the diagnostic value of integrating histopathological, clinical, and radiological evidence to better understand disease pathogenesis.